Legal Regulations for Customer Protection of Financial Products in Indonesia - Alvin Hamzah Nasution (Rechtsvinding, 2026)
The rapid and complex development of the financial services sector in Indonesia has given rise to a variety of financial products with varying characteristics and levels of risk. This situation places customers in a vulnerable position due to information asymmetry, imbalanced bargaining power, and limited understanding of the legal aspects and risks of financial products. Therefore, legal regulations regarding customer protection are a fundamental need to ensure legal certainty, justice, and the protection of customer rights. This article aims to analyze the legal regulations for customer protection for financial products in Indonesia, emphasizing the normative basis, the role of supervisory authorities, and the forms of preventive and repressive legal protection. This research uses a normative legal method with a statutory and conceptual approach. The results show that customer protection has been regulated in various regulations, but its implementation still faces obstacles in terms of financial literacy, law enforcement, and the effectiveness of dispute resolution.